Consumer Responses to Corporate Social Responsibility (CSR) in China - Tian, Zhilong (Journal of business ethics, 2011)
This research explores how consumers respond to Corporate Social Responsibility (CSR) in China with a multiproduct, comparative survey. Empirical results conclude that (1) Chinese consumers, who show a high level of awareness and trust of CSR, are more likely to transform a good CSR record into positive corporate evaluation, product association, and purchase intention; (2) Consumer responses to CSR vary across different product categories. Those firms selling experience products (vs. search and credence products) are more likely to gain consumers’ positive product associations and purchase support through CSR practices; and (3) The relationships between consumer demographics and their CSR responses are not linear, and those consumers with a middle level of age and income would respond to CSR more positively. Managerial implications are provided.